Spatiotemporal patterns and influencing factors of coupling coordination development of ecosystem services and urbanization: a case of western border counties in China - Liu, Luyao; Shi, Yungui; Meng, Qun (Frontiers in Public Health, 2025)
IntroductionThe spatial distribution of border regions highly overlaps with key ecological function zones and economically underdeveloped areas, making the coordination between urbanization and ecosystem service value (ESV) crucial.MethodsTaking China's western border counties as a case study, this study explores the spatiotemporal variation characteristics of ESV, urbanization levels, and their coupling coordination relationship. By applying the Obstacle Degree Model and the geodetector analysis, we identify the factors that obstruct and drive the coordinated development of the ESV-urbanization coupling system from both internal and external perspectives.Results(1) From 2000 to 2020, ESV in China's western border counties declined gradually, while the urbanization increased with significant spatial imbalances in development. (2) In most border counties, the coupling coordination degree (CCD) of ESV and urbanization was either mildly or severely unbalanced, and a growing number of counties experienced lagging ESV. In particular, some counties exhibited synchronous declines in both ESV and urbanization, posing a significant threat to regional sustainable development. (3) The main obstacle factors of CCD include social security, industrial structure and ecological regulation functions, while the primary driving factors are precipitation, temperature, and net primary productivity (NPP). (4) The interaction of tourism, stable ecological areas and government actions with other factors significantly enhances the driving effect on CCD in border counties.ConclusionThis study provides policy recommendations and a practical basis for promoting synergistic development between ESV and urbanization in China's western border counties and other similar border regions.